PENGUBAHAN KOMPOSISI CADANGAN MAKANAN BENIH KEDELAI DENGAN PERLAKUAN NITROGEN DAN FOSFOR - Rudi Hartawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
Some theories suggest that the important role of food reserves to maintain seed quality. On soybean seed, food reserves in the form of protein, carbohydrates, and fats. Generally researchers claim that high fat will reduce the quality and vitality of seeds in storage. Setting up food composition will maintain the quality and vitality of seeds in storage. Composition of food reserves is an equilibrium, increase one portion of food reserves would lower portion of the otherFood reserves play an important role in determining the quality of soybean seed. Deposit composition can be modified by eating nutrients nitrogen and phosphorus, and association with Rhizobium bacteria. Setting up the composition of foods believed to increase the quality and viability of soybean seed.The results showed that soybean growth variables measured with ILD, LAB, LTR, and BKA influenced by nitrogen and phosphorus, both single and two-factor interactions. Variables BKA instrumental in increasing seed production. The composition of the food reserves are also affected by the interaction between nitrogen and phosphorus except carbohydrates. Increase in protein content followed by a decrease in fat content in the seed, whereas carbohydrate content did not experience the difference. It is generally known that the root dry weight, production, 1000 grain weight and seed protein obtained at optimal combination of nitrogen 45 kg ha-1 and phosphorus at 90 kg ha-1. Information from this trial will be better if done testing the model composition and food reserves to do with the ability of seeds to survive naturally in storage.Keywords: food storage, enzymes, seed production